Assessment of Utilizing Gypsum and Clays in Manufacturing Thermal Insulators - Tamar-Agha1, Mazin Y.; Mohamed, Suzan N. D. (Sulaimani Journal for Pure and Applied Sciences, 2007)
Utilization of gypsum, clay and marl from the Fatha Formation (Middle Miocene) in Darbandi Bazian - Sulaimani Government were assessed for manufacturing thermal insulators. The raw materials were analyzed mineralogically, chemically and physically. They were then crushed and ground to less than 125 pm. Ten batches were prepared by mixing 70/30, 60/40,50/50, 40/60 and 30/70 weight % ratio of gypsum to clay or marl, 210 test samples were formed by semi-dry pressing, oven dried at 105C and fired at 1000, 1050 and 11100 oC with a rise of 100 oC/h and one hour soaking time. The fired briquettes were tested later on to assess their suitability as thermal insulator. The results of physico-mechanical tests showed that the linear shrinkage is 0.13 to 3.75 o/o, apparent porosity is 30.8 to 41.4 %, water absorption 17.4 to 28.0 %, bulk density is 1.48 to 1.78 g/cm3, compressive strength is 100.1 to 438.5 kg/cm2 and modulus of rupture is 31.5 to 76,5 kg/cm2. Meanwhile, four samples were selected to investigate their thermal conductivity (k) and found that it ranges between 0.3 and 0.4 w/m. oC, which reveals that they are good insulators.
Keywords: Thermal insulators; structural bricks; ceramics; gypsum